Design and Analysis of Propeller for High-Altitude Search and Rescue Unmanned Aerial Vehicle. (23rd January 2021) - Dahal, Chiranjivi; Dura, Hari Bahadur; Poudel, Laxman
Abstract : The commercially available unmanned aerial vehicles are not good enough for search and rescue flight at high altitudes. This is because as the altitude increases, the density of air decreases which affects the thrust generation of the UAV. The objective of this research work is to design thrust optimized blade for an altitude range of 3, 000–5, 000 m with a density of air 0.7364 kg/m 3, respectively, and perform thrust analysis. The property of aluminum alloy 1, 060 being lightweight is chosen for designing and testing of blade. The blade element theory-based design and analysis code was developed, and user-friendly aerodynamic inputs were used to obtain the desired outputs. The geometry designed for an altitude range of 3, 000-5, 000 m faced the total stress of 6.0 MPa which was at 70% of the blade span. This stress is within the limit of yield strength of the aluminum alloy, 28 MPa. The modal analysis shows the first natural frequency occurs at around 12, 000 RPM which is safe for operating the blade at 0-5, 000 RPM. Experimental analysis of the blade gave a thrust of 0.92 N at 2, 697 RPM at 1, 400 m. The analytical solution for thrust with the same conditions was 1.7 N with 85.6% efficiency. The validation of experimental results has been done by the CFD analysis. The CFD analysis was performed in ANSYS CFX which gave a thrust value of 2.27 N for the same boundary conditions. Thus, the blade designed for high altitude SAR UAV is structurally safe to operate in 0-5, 000 RPM range, and its use in search missions could save many lives in the Himalayas.